2022
DOI: 10.1111/afe.12493
|View full text |Cite
|
Sign up to set email alerts
|

Ants are effective pollinators of common buckwheat Fagopyrum esculentum

Abstract: Proper management of wild pollinators of agricultural crops requires identification of effective pollinator species. Although non‐bee pollinators are gaining increasing attention, small ground‐dwelling insects such as ants are often deemed ineffective. However, our previous study found a positive correlation between ant visitations to flowers and seed set in the distylous crop common buckwheat, suggesting a potential role of ants as effective pollinators. In this study, we aimed to confirm the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…S5 ). Ants are major pollinators of some wild plants 66 , 67 , but ant pollination of crop plants has not been reported, except for mangoes in the tropics 68 . However, our recent experimental study revealed a significant contribution to buckwheat pollination by ants 69 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S5 ). Ants are major pollinators of some wild plants 66 , 67 , but ant pollination of crop plants has not been reported, except for mangoes in the tropics 68 . However, our recent experimental study revealed a significant contribution to buckwheat pollination by ants 69 .…”
Section: Discussionmentioning
confidence: 99%
“…However, our recent experimental study revealed a significant contribution to buckwheat pollination by ants 69 . Ants do not move long distances, and pollination may be limited to a small spatial range 68 . However, given that buckwheat is cultivated densely and two types of distylous flowers are close by, pollen transfer by ants is likely to be prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…lugubris ), and most individuals were not observed moving between plants. Ants were also excluded from analysis as preliminary observations demonstrated little movement between plants and they are not considered pollinators in some systems (Beattie, 2006; Beattie et al, 1984, but see Natsume et al, 2022, Gras et al, 2016 and Das & Das, 2023). We hereafter refer to Hymenoptera as bees and wasps.…”
Section: Methodsmentioning
confidence: 99%